Fiqh Controversy Surrounding Jama’ and Qasar Prayers in the Modern Era - Nurjali; Niskaromah; Zaenal Abidin; Maimunah (Zabags International Journal of Islamic Studies, 2026)
Jama’ and qasar prayers are forms of rukhsah (legal concessions) granted in Islamic law to individuals facing specific circumstances, particularly travelers (musafir). However, with the passage of time, the application of this rukhsah has sparked various controversies, especially in light of the high mobility of modern society, advancements in transportation, and evolving concepts of “travel” (safar). This article aims to re-examine the fiqh-based concept of jama’ and qasar prayers in a contemporary context by exploring differences between classical scholars’ interpretations and modern scholars’ responses to new realities. The study employs a qualitative-descriptive approach using library research methods, analyzing classical fiqh sources (from the four major schools) as well as contemporary literature. The findings suggest that while the foundational principles of rukhsah remain relevant, there is a need for renewed ijtihad to contextually define the criteria for safar and emergency conditions so that Islamic law remains adaptable without compromising its normative authority.